Programa Nossocrédito : uma análise do processo de formulação e implementação da política de microcrédito do Estado do Espírito Santo - Giuberti, Inez Fávero Rigoni (2008)
This study examines the policy of microcredit in the state of Espírito Santo, called “NOSSOCRÉDITO”, from the processes of formulation and implementation of the Program, set up by the State’s government in August 2003, to its recent achievements, including the period between August 2003 and April 2008. It investigates the specifics of the program given the context (economic, political, social and cultural) in which it’s embedded, and its relationship with the emergence and spread of the microcredit phenomenon, started in the 1990’s. It explores the institution, its public character and the inter-state relations established between the participating institutions and between government and civil society. It presents the theoretical debate on the policy of extending small loans to "low income" people from two different concepts: mechanism to combat poverty x insertion of the poor in the practices of liberal capitalism. Uses primary data collected through semi-structured interviews, with key actors of the Program, and secondary data obtained through official documents and specialized academic literature on the subject. It opts for the qualitative approach as a method of research, and interprets the data using the content analysis. It concludes that the institutional arrangement built for the implementation of Nossocrédito introduced mechanisms that ensure the sustainability of the Program: robust source of resources; capillarity; dilution of costs between the partners and the supply of credit at a reduced rate. Despite its potential, it has limited scope and does not meet the needs of poorest population in the “low income" category.